A case of antithrombin replacement using recombinant human antithrombin in an adult patient supported with extracorporeal membrane oxygenation. Issue 8 (29th June 2015) - Lavandosky, Gerald J.
Key Clinical Message: In the critically ill patient on extracorporeal life support, antithrombin production and activity can be decreased and may require replacement to therapeutic levels in order to maintain appropriate anticoagulation and prevent thrombosis. Abstract : In the critically ill patient on extracorporeal life support, antithrombin production and activity can be decreased and may require replacement to therapeutic levels in order to maintain appropriate anticoagulation and prevent thrombosis.